Redesign of Primordial Museum and Archaeological Research Center in Cipari Archaeological Site Area, Kuningan Regency with Biophilic Architecture Approach - Tifanika Nadyan; Bambang Setyohadi Kuswarna Putra; Ardiyan Adhi Wibowo; Eko Budi Santoso (Universitas Negeri Semarang, 2024)
Indonesia is a paradise for archaeological research, proven by the many kinds of Pleistocene era artifact findings scattered throughout the country, including in Kuningan Regency. One of them is the finding of a megalithic site in Cipari Village, which is the only megalithic heritage archaeological site given more attention by the Kuningan Regency municipal government, with the establishment of the Cipari Archaeological Park Museum in 1976. Ironically, the archaeological museum building at Cipari Site is still relatively simple, and has not been able to follow the guidelines for establishing a museum. The existing building, which has an area of 80m², only contains temporary exhibition rooms, toilets and management rooms which are deemed unable to accommodate groups of tourists who often come from various educational institutions. So, a redesign is needed that is able to house a collection of artifacts as well as an archaeological research center to facilitate archaeologists and scientists, in researching artifacts that have been found in Kuningan and its surroundings. The primordial museum and archaeological research center is a building that stores and researches natural objects of ancient relics found in nature, so it is good if this building can be redesigned by considering its relationship with nature. Therefore, the biophilic architecture approach is deemed appropriate in the redesign of the museum building along with the archaeological research center or in other languages, the Primordial Museum and Archaeological Research Center in the Cipari Archaeology Site Area, Kuningan Regency. Data is also needed which includes primary and secondary data needs and then analyzed with five aspects of the approach, including functional, contextual, technical, performance and architectural aspects. The results will produce design recommendations for the Primordial Museum and Archaeological Research Center in the Cipari Antiquities Area, Kuningan Regency, West Java.